Prospective observations study protocol to investigate cost-effectiveness of various prenatal test strategies after the introduction of noninvasive prenatal testing - So Yeon Kim; Seung Mi Lee; Jong Kwan Jun; You Jung Han; Min Hyoung Kim; Jae-Yoon Shim; Mi-Young Lee; Soo-young Oh; JoonHo Lee; Soo Hyun Kim; Dong Hyun Cha; Geum Joon Cho; et al. (BMC, 2018)
Abstract Background Among the non-invasive screening methods for the identification of fetal aneuploidy, NIPT (non-invasive prenatal testing) shows the highest sensitivity and specificity in high-risk pregnancies. Due to the low false positive rate of NIPT, it is assumed that the implementation of NIPT as a primary screening method may reduce the number of invasive fetal tests and result in a similar or lowered cost in the overall detection of Down syndrome. However, most previous studies are based on theoretical economic analysis. This study aims to determine the cost effectiveness of various prenatal test strategies, including NIPT, in real clinical settings in both low risk and high risk pregnancies. Methods/design In this prospective observational study, women (< 24 weeks) with singleton or twin pregnancies will be enrolled in 12 different healthcare institutions. The participants will be grouped based on the risks of fetal chromosomal abnormalities and will be counseled on the various screening or diagnostic methods, including NIPT, according to the aneuploidy risk. The final decision on screening or diagnostic methods will be made by patients after counseling. Questionnaires regarding factors affecting the decision on prenatal test will be answered by the participants and physicians. The economic analysis on final total costs will be compared according to the various prenatal test strategies. Discussion The results of present study are expected to have a significant impact on national policies in determining Korean prenatal screening test strategies and to help in developing novel and effective prenatal screening tests in the future.